Технология формирования программы развития как системы годовых планов предприятия на основе ключевых показателей деятельности - Москаленко, Валентина Владимировна; Захарова, Татьяна Вячеславовна; Фонта, Наталия Григорьевна (Consilium limited liability company, Poland, 2015)
В статье рассмотрен процесс формирования стратегических показателей эффективности, предложена технология формирования годовых плановых показателей деятельности на основе декомпозиции стратегических ключевых показателей эффективности до первичных показателей, отражаемые в годовой отчётности предприятия.

The article describes the technology of the strategic development program formation based on the business-oriented approach. The basis of the program is the system of the planned Key Performance Indicators. At the strategic level the system is represented as a set of Key Performance Indicators, at the tactical and operational levels – as a set of planned indicators of operating, investing and financing activities. Strategic Key Indicators are formed within a strategic map creation using the conception of Balanced Scorecard. These indicators are interconnected and characterize the following aspects of a company’s functioning as Finance, Customers, Business-Processes, and Staff. The procedure of the decomposition of strategic level Key Performance Indicators into annual primary indicators by operating, investing and financing enterprise activities is proposed in the paper. The process of the program formation includes the procedure of required resources determination for achieving planned annual primary indicators by activities as well. After determining the system of planned indicators, the enterprise investment policy and corresponding investment projects portfolio are elaborated. For each investment project the financing scheme is formed and as a result a funding plan of the development program is created. The process of development program formation is iterative. At each stage of the process the analysis of the possibility of the development strategy achieving and adjustment of the strategic indicators taking into account the company’s opportunities is carried out.
Technology of formation of development program as a system of company's annual plans based on key performance indicators
Keywords: стратегическое управление; инвестиционная деятельнсть; оперативные планы; тактические планы; финансовая деятельность; strategy map; key performance indicators; balanced scorecard; primary performance indicators